Trauma-informed Collaborative Care for African American Primary Care Patients in Federally Qualified Health Centers: A Pilot Randomized Trial. Issue 3 (28th March 2022) - Meredith, Lisa S.; Wong, Eunice; Osilla, Karen Chan; Sanders, Margaret; Tebeka, Mahlet G.; Han, Bing; Williamson, Stephanie L.; Carton, Thomas W.
Abstract : Background: African Americans have nearly double the rate of posttraumatic stress disorder (PTSD) compared with other racial/ethnic groups. Objective: To understand whether trauma-informed collaborative care (TICC) is effective for improving PTSD among African Americans in New Orleans who receive their care in Federally Qualified Health Centers (FQHCs). Design and Method: In this pilot randomized controlled trial, we assigned patients within a single site to either TICC or to enhanced usual care (EUC). We performed intent to treat analysis by nonparametric exact tests for small sample sizes. Participants: We enrolled 42 patients from October 12, 2018, through July 2, 2019. Patients were eligible if they considered the clinic their usual source of care, had no obvious physical or cognitive obstacles that would prevent participation, were age 18 or over, self-identified as African American, and had a provisional diagnosis of PTSD. Measures: Our primary outcome measures were PTSD measured as both a symptom score and a provisional diagnosis based on the PTSD Checklist for DSM-5 (PCL-5). Key Results: Nine months following baseline, both PTSD symptom scores and provisional PTSD diagnosis rates decreased substantially more for patients in TICC than in EUC. The decreases were by 26 points in EUC and 36 points in TICC for symptoms ( P =0.08) and 33% in EUC and 57% in TICC for diagnosis rates ( P =0.27). We found no effects for mediator variables. Conclusions: TICC shows promise for addressing PTSD in this population. A larger-scale trial is needed to fully assess the effectiveness of this approach in these settings.